2023
DOI: 10.1186/s12967-023-04342-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of immunotherapy mediated by apoptotic bodies, microvesicles and exosomes: apoptotic bodies’ unique anti-inflammatory potential

Jing Wen,
Dale Creaven,
Xiangshu Luan
et al.

Abstract: Immunotherapy, including immunostimulation and immunosuppression, has seen significant development in the last 10 years. Immunostimulation has been verified as effective in anti-cancer treatment, while immunosuppression is used in the treatment of autoimmune disease and inflammation. Currently, with the update of newly-invented simplified isolation methods and the findings of potent triggered immune responses, extracellular vesicle-based immunotherapy is very eye-catching. However, the research on three main t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 157 publications
0
4
0
Order By: Relevance
“…Additionally, we found that the isolated exosome preparations in this study also contained various extracellular vesicles such as microvesicles and apoptotic bodies. Extracellular vesicles can be subdivided into exosomes, microvesicles, and apoptotic bodies according to their origin [ 45 ]: exosomes are derived from intracellular endosomal compartments, while microvesicles are particles released from the surface of cells, and apoptotic bodies are released by cells undergoing apoptosis [ 46 ]. Since each of these types of vesicles has a wide size distribution, it is difficult to separate them using only centrifugation [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that the isolated exosome preparations in this study also contained various extracellular vesicles such as microvesicles and apoptotic bodies. Extracellular vesicles can be subdivided into exosomes, microvesicles, and apoptotic bodies according to their origin [ 45 ]: exosomes are derived from intracellular endosomal compartments, while microvesicles are particles released from the surface of cells, and apoptotic bodies are released by cells undergoing apoptosis [ 46 ]. Since each of these types of vesicles has a wide size distribution, it is difficult to separate them using only centrifugation [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that EVs extend their reach beyond cancer immunotherapy. Research is actively exploring the use of EVs derived from immune regulatory T cells and stem cells to suppress unwanted immune responses [ 160 171 ]. This versatility highlights the exiting possibilities of EVs in tuning the immune system, offering the potential to both stimulate and dampen immune activity depending on the therapeutic need.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptotic bodies (500-4000 nm) are produced by apoptotic cells and are characterized by the presence of organelles within the vesicles ( 127 ). Exosomes, STBMs, and apoptotic bodies have a similar lipid bilayer membrane and carry genetic and protein cargo associated with the inflammatory reaction in PE ( 128 ). However, there are some subtle differences in their roles in PE.…”
Section: Roles Of Exosomes In Pementioning
confidence: 99%